The Ritual of Khanduri Bungong Kayèe (An Ethnographic Study in West Labuhan Haji-South Aceh) - Manan Abdul (Antropologi Indonesia, 2013)
The khanduri of the tree blossom is performed in Jumadil Akhir (the sixth Islamic lunar month). The khanduri is held for fruit-bearing trees. It aim is tu ensure that the trees will bear fruit andtheir blossoms will not fade and fall onto the round prematurely, thatthey will not be attackedby pests so that they will contribute to the livelihood of human beings. This research is a fieldresearch and its data were obtained through meticulous observation and in depth interview withkey informants. The result of the research shows that it is the winds that cause the trees to blossom. The village people performed this ritual in order that the condition of fertility of fruit-bearing trees is safeguarded but the fertility is dependent upon much more important factorrs than just the willingess of the individual family to perform the ritual. The fertility of the tree is dependent upon collective village performance, dependent upon respecting jinn, dependent upon just leadership and dependent upon adat, particularly regarding probihition adn incest which are regarded as a major infringement on community life.Key words: ritual of khanduri bungong kayèe, the influence of seasons and winds as well ascondition of fertility of fruit-bearing trees